Almost Reduction and Perturbation of Matrix Cocycles - Navas-Flores, A (Elsevier Masson SAS, 2014)
In this note, we show that if all Lyapunov exponents of a matrix cocycle vanish, then it can be perturbed to become cohomologous to a cocycle taking values in the orthogonal group. This extends a result of Avila, Bochi and Damanik to general base dynamics and arbitrary dimension. We actually prove a fibered version of this result, and apply it to study the existence of dominated splittings into conformal subbundles for general matrix cocycles. © 2013 Elsevier Masson SAS. All rights reserved.